IMPROVING STUDENTS™ ACHIEVEMENT IN WRITING PROCEDURE TEXTS BY USING VIDEOS - Simbolon, Widya Ladeci; Saragih, Amrin (TRANSFORM: Journal of English Language Teaching and Learning, 2013)
ABSTRACT This study deals with the students™ achievement improvement in writing procedure texts by using videos by applying classroom action research. The subjects of this research were 38 students of class X-1 SMA TELADAN MEDAN. After analyzing the data in two cycles of classroom action research, it was found there was an improvement of students™ mean score from 60.44 in assessment before applying video became 68.52 in cycle I and improved again became 78.89 in cycle II. It means that the use of video significantly improves the students™ achievement in writing procedure texts. Keywords: writing, procedure text, action research, videos, X-I SMA Teladan Medan.